-2(x-7)-(x+5)=5

Simple and best practice solution for -2(x-7)-(x+5)=5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(x-7)-(x+5)=5 equation:


Simplifying
-2(x + -7) + -1(x + 5) = 5

Reorder the terms:
-2(-7 + x) + -1(x + 5) = 5
(-7 * -2 + x * -2) + -1(x + 5) = 5
(14 + -2x) + -1(x + 5) = 5

Reorder the terms:
14 + -2x + -1(5 + x) = 5
14 + -2x + (5 * -1 + x * -1) = 5
14 + -2x + (-5 + -1x) = 5

Reorder the terms:
14 + -5 + -2x + -1x = 5

Combine like terms: 14 + -5 = 9
9 + -2x + -1x = 5

Combine like terms: -2x + -1x = -3x
9 + -3x = 5

Solving
9 + -3x = 5

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-9' to each side of the equation.
9 + -9 + -3x = 5 + -9

Combine like terms: 9 + -9 = 0
0 + -3x = 5 + -9
-3x = 5 + -9

Combine like terms: 5 + -9 = -4
-3x = -4

Divide each side by '-3'.
x = 1.333333333

Simplifying
x = 1.333333333

See similar equations:

| 12x+x=130 | | r^2-34r+8=0 | | 2J(-5J^3+4J^2-20)-6J^2(-4J^2+3J+7)= | | 0.125x+16=4+0.125 | | 4x^2+30x=4 | | 81/8-6 | | x^2+(12-b)x+b=0 | | 4x^2+6x+0=0 | | 4x+17+5x+5+x+x=132 | | 3p+4=25 | | x^3+7x^2-14x+7=0 | | 21/5x-y=16/5 | | (5+2)*3= | | 4(5x-9)= | | x+.145x=17063 | | x+.145x=21063 | | 0=13b^2-60b+21 | | 9t-3=4+-2 | | 2ax+2by-a^2-b^2-7=2x-3y+10 | | 3x-4+2x+8=5x-7 | | x-9/4=20.4 | | -13c=-56 | | 11x-44=0 | | (3x-5)*(x-1/5)*x=0 | | -3y+45=3(3y-5) | | 6x=11/12 | | 0.5(a-8)=1.3(a+6) | | K/4-4 | | N/33 | | 13a+1=14 | | 5(x-3)-3x=3(x-5)-x | | 10a-15=-4 |

Equations solver categories